O campo de estudos sobre arranjos produtivos locais nos periódicos brasileiros - Coan, Fernanda Mosseline Josende (Universidade do Vale do Rio dos Sinos, 2011)
The aggressive competition originated in the international market has led companies to seek for strategies to stay on the market; therefore, in such a scenario, cluster has emerged as a phenomenon which enables companies to achieve greater competitiveness. However, a compilation to carry out a study on the Brazilian scientific production on local productive arrangements has been made necessary. Thus, this study aims to analyze the scientific production in Clusters which were published on scientific journals of management, economics and social sciences in Brazil, from 2001 to 2010. It has been understood that this goal is proved relevant because, through it, we become familiar with the landscape of local productive arrangements which will enable an advancement of the theory of Cluster. to carry out this study, a meta-analysis i n 57 articles extracted from 22 magazines was performed, by making use of parameters such as the identification of the frequency of approaches adopted in the articles, the origin of the used bibliographies, the most used authors frequency and their works, in as much as the frequency of pre-selected categories. Besides, content analysis of those pre-selected articles was carried out, plus the analyses of contribution of each article from seven categories ending with the creation of an agenda for future study. Among the results, we highlight the harmony between the content in the literature as well as in the articles, the evolution and the variety of subjects connected with the theme, the frequent used of international publications and the predominance of empiric articles applicable into 83 Brazilian Clusters.
Keywords: Arranjos produtivos locais; Meta-análise; Periódicos brasileiros; Cluster; Meta-analyisis; Brazilian journals; ACCNPQ::Ciências Humanas::Sociologia